Geometry and Construction of Upper Crustal Intrusions; Sawtooth Ridge, Henry Mountains, Southern Utah. - Eischen, Tanner E (East Carolina University)
The plumbing systems of volcanos are commonly constructed by interconnected, upper crustal sheet intrusions (i.e. dikes and sills). Active systems and the processes that contribute to their construction are difficult to study directly, but it is possible to indirectly observe these processes by studying ancient upper crustal intrusions now exposed at the surface. The Sawtooth Ridge intrusion is one such shallow, Oligocene intrusion located on the northeastern margin of Mount Hillers in the Henry Mountains of southern Utah. While many adjacent and similarly sized intrusions are well understood (Maiden Creek Sill, Trachyte Mesa laccolith, Black Mesa Bysmalith), previous works concerning the Sawtooth Ridge intrusion have been inconclusive. Through a combination of field and lab techniques, constraints are provided on the emplacement history and subsurface geometry of the Sawtooth Ridge intrusion, and subsequently, the processes responsible for its construction. Field mapping suggests the first- and second-order geometries of the Sawtooth Ridge intrusion are more complex than a traditional dike or sill. The intrusion extends approximately 4 km from the northeast flank of Mount Hillers with an irregular, step-like upper surface. Lobes of igneous rock separate islands of sedimentary host rock and several dikes extend perpendicularly from the main crest of the intrusion. Along with geochemical data, this suggests that the intrusion was built incrementally through the injection of two or more batches of magma. Data from field observations and petrofabric analysis suggest that magma from the Mount Hillers intrusive center was transported sub-vertically towards the NE to construct the Sawtooth Ridge intrusion. Magnetic anomaly modelling suggests that the subsurface geometry of the main intrusive body is most accurately represented by a series of parallel, dike/tube hybrids. Data suggest a three-step model of construction in which a series of parallel dike/feeder tubes intruded from the southwest. As the magma ascended to a critical elevation, the minimum stress direction was no longer oriented horizontally, causing magma to transition to a tube- or tongue-like propagation. As this intrusive stage inflated to a critical aspect ratio, principal stress directions rotated again causing magma to be emplaced as vertical dikes extending perpendicularly from the main intrusive body.
Keywords: Intrusions (Geology)--Utah--Henry Mountains; Igneous rocks--Inclusions--Utah--Henry Mountains; Geology, Structural--Utah--Henry Mountains